A thermoplastic carbon fiber reinforced nylon composite material and preparation method thereof
Through the chemical modification of modified carbon fibers and flame retardants, a spatial network structure is formed, which solves the problems of poor interface bonding force of thermoplastic carbon fiber reinforced nylon composite materials and environmental pollution of traditional flame retardants, and achieves efficient and safe flame retardant effects and excellent mechanical properties.
Patent Information
- Application Number
- CN202510041303.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The interface bonding of existing thermoplastic carbon fiber reinforced nylon composites is poor, which affects its comprehensive performance, and traditional flame retardants have the risk of environmental pollution.
Through the preparation of modified carbon fibers, the carbon-carbon double bonds on its surface are increased, and the chemical effects of crosslinking agents and flame retardants are combined, the interface compatibility between modified carbon fibers and raw materials such as nylon resin is improved, and the spatial network structure is formed through the esterification and amidation reaction of flame retardants, and the stability and dispersion of flame retardants are improved.
It significantly improves the interface compatibility and flame retardant properties of composite materials, enhances its mechanical properties and stability, and avoids the use of halogen and reduces the risk of environmental pollution.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermoplastic composite materials, and in particular, relates to a thermoplastic carbon fiber reinforced nylon composite material and a preparation method thereof. Background Art
[0002] Carbon fiber is a new type of reinforcement material with the characteristics of high strength, high modulus, large specific surface area and aspect ratio, high conductivity, etc. Nylon is a macromolecule containing amide groups in its molecule. Reinforced nylon composite materials are widely used in the production of various products. The organic combination of these two materials can significantly improve the mechanical properties of the composite material and expand its application range.
[0003] However, the compatibility and affinity between carbon fiber and thermoplastic resin are poor, making it difficult to form chemical bonds and the interface adhesion is poor, which affects the comprehensive performance of the composite material.
[0004] Chinese patent CN102746661A discloses a method for preparing a flame-retardant carbon fiber reinforced nylon composite material. The raw materials of the composite material include 70-76 parts of nylon 610 resin, 21-27 parts of nylon 6 resin, 0.7-1.4 parts of coupling agent, 15-25 parts of filler, 17-23 parts of flame retardant, 0.3-0.7 parts of antioxidant, 20-28 parts of carbon fiber and 18-23 parts of glass fiber. Although the composite material has excellent flame retardant properties, the flame retardant is decabromodiphenylethane, which is a halogen-containing flame retardant, harmful to the environment, and easy to migrate and escape. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a thermoplastic carbon fiber reinforced nylon composite material and a preparation method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A thermoplastic carbon fiber reinforced nylon composite material comprises the following raw materials in parts by weight: 90-100 parts of nylon resin, 20-30 parts of modified carbon fiber, 20-30 parts of filler, 1-3 parts of coupling agent, 15-25 parts of flame retardant, 0.5-1.5 parts of antioxidant, 0.5-1.5 parts of ultraviolet absorber and 0.01-0.1 parts of cross-linking agent.
[0008] Furthermore, the nylon resin is one or more of nylon 6 resin, nylon 46 resin, nylon 610 resin, and nylon 1010 resin.
[0009] Furthermore, the modified carbon fiber is prepared by the following steps:
[0010] Add carbon fiber and nitric acid with a mass fraction of 65% into a three-necked flask, heat to 80℃, reflux and stir for 6h, cool to room temperature after the end, filter and wash with deionized water until the filtrate is neutral, and dry the filter residue at 110℃ for 12h to obtain pretreated carbon fiber; add pretreated carbon fiber, maleic anhydride, DMAP (4-dimethylaminopyridine) and DMF (N,N-dimethylformamide) into a three-necked flask, stir and heat to 50℃, keep warm for 12h, filter after the reaction, wash with anhydrous ethanol, and dry at 80℃ for 6h to obtain modified carbon fiber; the dosage ratio of carbon fiber and nitric acid is 10g:250mL; the dosage ratio of pretreated carbon fiber, maleic anhydride, DMAP and DMF is 35g:6.3g:0.65g:240mL.
[0011] The surface of the pretreated carbon fiber obtained by nitric acid treatment contains abundant hydroxyl functional groups, which can react with maleic anhydride under the catalysis of 4-dimethylaminopyridine to undergo esterification reaction, and the surface of the prepared modified carbon fiber contains carbon-carbon double bonds. The carbon-carbon double bonds on the surface of the modified carbon fiber can react chemically with the carbon-carbon double bonds on the surface of the flame retardant under the action of the crosslinking agent, which can increase the interfacial compatibility between the modified carbon fiber and raw materials such as nylon resin, and also increase the stability and dispersion of the flame retardant.
[0012] Furthermore, the filler is one or more of calcium carbonate, talcum powder, glass fiber, barium sulfate, and calcium sulfate.
[0013] Furthermore, the coupling agent is one or more of vinyltrimethoxysilane, vinyltriethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane.
[0014] Under the action of the silaneoxy group of the coupling agent, the coupling agent is grafted on the surface of the filler, thereby improving the dispersion of the filler. At the same time, the carbon-carbon double bonds on the surface of the filler can react chemically with the carbon-carbon double bonds on the surface of the flame retardant and the carbon-carbon double bonds on the surface of the modified carbon fiber under the action of the cross-linking agent, which can further increase the interface compatibility of the filler and modified carbon fiber with raw materials such as nylon resin, and further increase the dispersion and stability of the flame retardant.
[0015] Furthermore, the flame retardant is prepared by the following steps:
[0016] S1. Add flame retardant FRC-2 (3-[(hydroxymethyl)amino]-3-oxopropylphosphonic acid-dimethyl ester), DMAP (4-dimethylaminopyridine) and chloroform to a dry three-necked flask, stir and heat to 60°C, then slowly add maleic anhydride, react for 12 hours after the addition is completed, filter and remove the precipitate after the reaction is completed, wash the filtrate with saturated brine, quickly dry with anhydrous magnesium sulfate, and distill under reduced pressure to obtain intermediate 1; the amount ratio of flame retardant FRC-2, maleic anhydride, DMAP and chloroform is 23.2g:12.4g:0.27g:240mL;
[0017] Under the catalytic action of DMAP, the molar ratio of flame retardant FRC-2 to maleic anhydride is controlled to be 1:1.1-1.2, and then flame retardant FRC-2 and maleic anhydride undergo esterification reaction under heating. The reaction process is as follows:
[0018]
[0019] S2. Under nitrogen protection, add intermediate 1, EDC (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride), NHS (N-hydroxysuccinimide) and DMF (N,N-dimethylformamide) into a dry brown three-necked flask, stir to dissolve and then heat to 50°C, then slowly add 2,4-diamino-6-diallylamino-1,3,5-triazine, keep the temperature for 6 hours, cool to room temperature after the reaction, and distill under reduced pressure to obtain a flame retardant; the amount ratio of intermediate 1, 2,4-diamino-6-diallylamino-1,3,5-triazine, EDC, NHS and DMF is 24.7g:8g:3.1g:1.8g:240mL.
[0020] The molar ratio of intermediate 1 to 2,4-diamino-6-diallylamino-1,3,5-triazine is controlled to be 2.05-2.1:1, and the -COOH of intermediate 1 and the -NH2 of 2,4-diamino-6-diallylamino-1,3,5-triazine undergo amidation reaction under the action of EDC and NHS. The reaction equation is as follows:
[0021]
[0022] Flame retardants contain rich nitrogen and phosphorus flame retardant elements and do not contain any halogen. The synergistic effect of nitrogen and phosphorus elements gives composite materials an efficient and safe flame retardant effect. Phosphorus provides an acid source, which reacts with polymer materials to promote the formation of carbonized products; nitrogen provides a gas source, which can make the system expand and foam, and also promotes the formation of the carbonized layer to form porous foam carbon.
[0023] The flame retardant contains multiple terminal carbon-carbon double bonds, which can produce chemical reactions with the carbon-carbon double bonds on the modified carbon fibers and fillers during the melting process under the action of a cross-linking agent, thereby cross-linking the flame retardant with the modified carbon fibers and fillers to form a spatial network structure. The flame retardant, the modified carbon fibers and the fillers are all stably present in the composite material and fully exert their functions. Therefore, the composite material of the present invention has efficient and safe flame retardant effects and excellent and stable mechanical properties.
[0024] Furthermore, the antioxidant is one or more of antioxidant 1076, antioxidant 1010, antioxidant 1098, antioxidant 168, and antioxidant DLTP.
[0025] Furthermore, the ultraviolet absorber is one or more of the ultraviolet absorber UV-P, the ultraviolet absorber UV-9, and the ultraviolet absorber UV-531.
[0026] Furthermore, the cross-linking agent is one or more of benzoyl peroxide, dicumyl peroxide, and di-tert-butyl peroxide.
[0027] A method for preparing a thermoplastic carbon fiber reinforced nylon composite material comprises the following steps:
[0028] The raw materials are weighed according to weight and all the raw materials are fully stirred until they are uniformly mixed, and then put into a twin-screw extruder for melt extrusion to obtain a thermoplastic carbon fiber reinforced nylon composite material.
[0029] Beneficial effects of the present invention: There is interaction between the modified carbon fiber, filler and flame retardant of the present invention, so they are cross-linked to form a spatial network structure, and then the modified carbon fiber, filler and flame retardant can be highly dispersed and stably present in the composite material, and the interface compatibility with the nylon resin is greatly improved, so the three can give full play to their own role. Therefore, the composite material of the present invention has efficient and safe flame retardant effect and excellent and stable mechanical properties. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1, preparing modified carbon fiber, the specific steps are as follows:
[0032] 10g of carbon fiber and 250mL of 65% nitric acid were added to a 500mL three-necked flask, heated to 80℃, refluxed and stirred for 6h, cooled to room temperature after the reaction, filtered and washed with deionized water until the filtrate was neutral, and the filter residue was dried at 110℃ for 12h to obtain pretreated carbon fiber; 35g of pretreated carbon fiber, 6.3g of maleic anhydride, 0.65g of DMAP and 240mL of DMF were added to a 500mL three-necked flask, stirred and heated to 50℃, kept warm for 12h, filtered after the reaction, washed with anhydrous ethanol, and dried at 80℃ for 6h to obtain modified carbon fiber.
[0033] Example 2, preparing a flame retardant, the specific steps are as follows:
[0034] S1. Add 23.2 g of flame retardant FRC-2, 0.27 g of DMAP and 240 mL of chloroform to a 500 mL dry three-necked flask, stir and heat to 60 ° C, then slowly add 12.4 g of maleic anhydride, react for 12 hours after the addition is completed, and filter to remove the precipitate after the reaction is completed. Wash the filtrate with saturated brine, quickly dry with anhydrous magnesium sulfate, and distill under reduced pressure to obtain intermediate 1;
[0035] S2. Under nitrogen protection, add 24.7 g of intermediate 1, 3.1 g of EDC, 1.8 g of NHS and 240 mL of DMF into a 500 mL dry brown three-necked flask, stir to dissolve and then heat to 50 °C, then slowly add 8 g of 2,4-diamino-6-diallylamino-1,3,5-triazine, keep warm for 6 h, cool to room temperature after the reaction is completed, and distill under reduced pressure to obtain a flame retardant.
[0036] Example 3, preparing a thermoplastic carbon fiber reinforced nylon composite material, the specific steps are as follows:
[0037] Weigh each raw material by weight and stir 90 parts of nylon 6 resin, 20 parts of modified carbon fiber prepared in Example 1, 10 parts of barium sulfate, 10 parts of calcium sulfate, 1 part of 3-(methacryloyloxy)propyltrimethoxysilane, 15 parts of flame retardant prepared in Example 2, 0.5 parts of antioxidant 1098, 0.5 parts of ultraviolet absorber UV-P, and 0.01 parts of diisopropylbenzene peroxide until the mixture is uniform, and then put into a twin-screw extruder for melt extrusion to obtain a thermoplastic carbon fiber reinforced nylon composite material.
[0038] Example 4, preparing a thermoplastic carbon fiber reinforced nylon composite material, the specific steps are as follows:
[0039] Weigh each raw material by weight and stir 49 parts of nylon 46 resin, 49 parts of nylon 610 resin, 25 parts of modified carbon fiber prepared in Example 1, 13 parts of talc, 13 parts of glass fiber, 2 parts of vinyl triethoxy silane, 20 parts of flame retardant prepared in Example 2, 0.8 parts of antioxidant 1076, 0.2 parts of antioxidant DLTP, 0.5 parts of ultraviolet absorber UV-P, 0.5 parts of ultraviolet absorber UV-9, and 0.06 parts of benzoyl peroxide until the mixture is uniform, and then put into a twin-screw extruder for melt extrusion to obtain a thermoplastic carbon fiber reinforced nylon composite material.
[0040] Example 5: Preparation of a thermoplastic carbon fiber reinforced nylon composite material, the specific steps are as follows:
[0041] Weigh each raw material by weight and stir 50 parts of nylon 6 resin, 50 parts of nylon 1010 resin, 30 parts of modified carbon fiber prepared in Example 1, 10 parts of calcium carbonate, 10 parts of talc, 10 parts of glass fiber, 1 part of vinyl trimethoxy silane, 1 part of vinyl triethoxy silane, 25 parts of flame retardant prepared in Example 2, 0.8 parts of antioxidant 1010, 0.5 parts of antioxidant 168, 0.2 parts of antioxidant DLTP, 1 part of ultraviolet absorber UV-9, 0.5 parts of ultraviolet absorber UV-531, and 0.1 parts of di-tert-butyl peroxide until the mixture is uniform, and then put into a twin-screw extruder for melt extrusion to obtain a thermoplastic carbon fiber reinforced nylon composite material.
[0042] Comparative Example 1: preparing a thermoplastic carbon fiber reinforced nylon composite material, the specific steps are as follows:
[0043] The remaining steps remain unchanged, except that the modified carbon fiber in Example 3 is replaced by carbon fiber without any treatment to prepare a thermoplastic carbon fiber reinforced nylon composite material.
[0044] Comparative Example 2: preparing a thermoplastic carbon fiber reinforced nylon composite material, the specific steps are as follows:
[0045] The remaining steps remain unchanged, only the flame retardant in Example 3 is replaced by ammonium polyphosphate to prepare a thermoplastic carbon fiber reinforced nylon composite material.
[0046] Performance Testing
[0047] The thermoplastic carbon fiber reinforced nylon composite materials prepared in Examples 3-5 and Comparative Examples 1-2 were subjected to the following performance tests, and the test results are shown in the following table:
[0048]
[0049] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0050] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A thermoplastic carbon fiber reinforced nylon composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 90-100 parts of nylon resin, 20-30 parts of modified carbon fiber, 20-30 parts of filler, 1-3 parts of coupling agent, 15-25 parts of flame retardant, 0.5-1.5 parts of antioxidant, 0.5-1.5 parts of ultraviolet absorber and 0.01-0.1 parts of cross-linking agent; Wherein, the modified carbon fiber is prepared by the following steps: Add carbon fiber and nitric acid with a mass fraction of 65% to a flask, heat to 80°C and stir for 6 hours, cool, filter, wash and dry to obtain pretreated carbon fiber; add pretreated carbon fiber, maleic anhydride, DMAP and DMF to a flask, heat to 50°C and react for 12 hours, filter, wash and dry to obtain modified carbon fiber; the amount ratio of carbon fiber to nitric acid is 10g:250mL; the amount ratio of pretreated carbon fiber, maleic anhydride, DMAP and DMF is 35g:6.3g:0.65g:240mL; The flame retardant is prepared by the following steps: S1. Add flame retardant FRC-2, DMAP and chloroform to a flask, stir and heat to 60°C, then slowly add maleic anhydride, react for 12 hours after the addition is completed, filter and remove the precipitate after the reaction is completed, wash the filtrate with saturated brine, quickly dry with anhydrous magnesium sulfate, and distill under reduced pressure to obtain intermediate 1; the amount ratio of flame retardant FRC-2, maleic anhydride, DMAP and chloroform is 23.2g:12.4g:0.27g:240mL; S2. Under nitrogen protection, add intermediate 1, EDC, NHS and DMF into a flask, stir and heat to 50°C, add 2,4-diamino-6-diallylamino-1,3,5-triazine, react for 6 hours, cool, and distill under reduced pressure to obtain a flame retardant; the amount ratio of intermediate 1, 2,4-diamino-6-diallylamino-1,3,5-triazine, EDC, NHS and DMF is 24.7g:8g:3.1g:1.8g:240mL; The filler is one or more of calcium carbonate, talcum powder, glass fiber, barium sulfate, and calcium sulfate; the coupling agent is one or more of vinyl trimethoxy silane, vinyl triethoxy silane, and 3-(methacryloyloxy)propyl trimethoxy silane; and the cross-linking agent is one or more of benzoyl peroxide, diisopropyl peroxide, and di-tert-butyl peroxide.
2. A thermoplastic carbon fiber reinforced nylon composite material according to claim 1, characterized in that: The nylon resin is one or more of nylon 6 resin, nylon 46 resin, nylon 610 resin and nylon 1010 resin.
3. The thermoplastic carbon fiber reinforced nylon composite material according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1076, antioxidant 1010, antioxidant 1098, antioxidant 168, and antioxidant DLTP.
4. The thermoplastic carbon fiber reinforced nylon composite material according to claim 1, characterized in that: The ultraviolet absorber is one or more of the ultraviolet absorber UV-P, the ultraviolet absorber UV-9 and the ultraviolet absorber UV-531.
5. The method for preparing a thermoplastic carbon fiber reinforced nylon composite material according to claim 1, characterized in that: The following steps are involved: The raw materials are weighed according to weight and all the raw materials are fully stirred until they are uniformly mixed, and then put into a twin-screw extruder for melt extrusion to obtain a thermoplastic carbon fiber reinforced nylon composite material.
Citation Information
Patent Citations
Preparation method of flame retardant carbon fiber reinforced nylon composite material
CN102746661A
Carbon fiber reinforcement non-bittern flame-proof nylon 66 and preparation method thereof
CN101139462A
Damp-heat aging resisting carbon fiber-reinforced nylon 66 compound material and preparation thereof
CN105295368A